2012
DOI: 10.5402/2012/454072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Viability and Proliferation Profiles on Macrophages Treated with Silica Nanoparticles In Vitro via Plate-Based, Flow Cytometry, and Coulter Counter Assays

Abstract: Nanoparticles (NPs) are known to interfere with many high-throughput cell viability and cell proliferation assays, which complicates the assessment of their potential toxic effects. The aim of this study was to compare viability and proliferation results for colloidal silica (SiO 2 NP; 7 nm) in the RAW 264.7 mouse macrophage cell line using three different techniques: plate-based assays, flow cytometry analysis, and Coulter counter assays. Our data indicate that CellTiter-Blue, XTT, and CyQuant plate-based ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In live dopaminergic neurons, lactate dehydrogenase is contained within the cell; however, upon membrane perforation, it is released into the cytoplasm. Thereby, lactate dehydrogenase levels in the cell supernatant are a reliable indicator of injury of dopaminergic neurons (22). Furthermore, reverse transcriptase polymerase chain reaction and western blot were also applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In live dopaminergic neurons, lactate dehydrogenase is contained within the cell; however, upon membrane perforation, it is released into the cytoplasm. Thereby, lactate dehydrogenase levels in the cell supernatant are a reliable indicator of injury of dopaminergic neurons (22). Furthermore, reverse transcriptase polymerase chain reaction and western blot were also applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…NPs were opsonized by serum proteins and agglomerated over time when exposed to cell culture media. 21,22 All NPs tested below the detection limit for endotoxin (0.25 EU/mL) for the concentrations used in this study.…”
Section: Nps Characterizationmentioning
confidence: 99%
“…In addition, a suspended culture was utilized for the majority of experiments for several reasons: 1) The suspended state tends to reduce NP assay interference. 21 2) In adherent cell cultures, the exact number of cells is not known at the initiation of the experiment. By utilizing cell suspensions, the amount of cells used in the assay may be fixed, thus more tightly controlling the ratio of cells/NP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been shown that NMs can interact with LDH and decrease enzyme activity, [108] likely through structural deformation of the enzyme, this could result in inaccurate results regarding cell viability whereby toxicity would be masked. [84,85] NM generation of ROS The physicochemical properties of some NMs enable them to undergo oxidation and produce ROS that can potentially reduce dyes to their fluorescent forms, [92,100] resulting in false positive tests of toxicity. For example, incubation of carbon-based NMs with 2 0 ,7 0 -dichlorodihydrofluorescin diacetate (DCFH-DA) (a highly oxidisable dye that is a commonly used as a marker of oxidative stress) results in the production of fluorescent 2 0 ,7 0 -dichlorodihydrofluorescein (DCF) molecules even when cells are not present (Fig.…”
Section: Optical Interferencementioning
confidence: 99%